Kualitas Pembelajaran dengan Kompetensi Pembuatan Instalasi Air Menggunakan Model Pembelajaran Kooperatif (Implementasi Kerja Siswa Kelas X BKP SMK Negeri 1 Balikpapan) - Djoharesmi Djoharesmi (Academia Publication, 2021)
This research article aims to describe the improvement of the learning process in the construction of tear installations for Basic Construction and Construction, and the improvement of student achievement in the construction of tear installations for the implementation of BKP. This research was conducted at SMK Negeri 1 Balikpapan. The results showed that the STAD type cooperative learning model in the Basic Construction and Implementation of BKP (Plambing) training courses was able to provide an increase in work competency assembling water installation pipes with a positive response based on an average of 78.17% (good) cycle I and cycle II. of 86.87% (good). From this average, it shows an increase in student competency results where from each group has shown positive competition in each group, Team Reducing with a difference of 30 points (Super Team), in cycle II Team Tee with a difference of 31 points (The Best Team).